(untitled) (Bangladesh Pharmaceutical Journal, 2018)
Five exotic dietary and medicinal spices (Trachyspermum ammi, Curcuma longa, Piper nigrum (Black pepper, Anacardium occidentate, Syzygium aromaticum) were studied for their metal contaminations, phenolic contents, antioxidant and antibacterial properties. White pepper contains maximum phenolic contents and black pepper showed higher antioxidant potential. Clove showed maximum antimicrobial potential (25-30 mm) against Escherichia coli and Staphylococcus aureus (18-21 mm). White pepper contained maximum phenolic contents. Estimation of metal contamination in spices indicated that K, Ca, Mg, Cu, Co, As, Hg, Mo were above the standard permissible limits (SPL), Cr, Ni and Cd within standard permissible limits, whereas, Fe, Zn, Mn and Pb were below standard permissible limits. Bangladesh Pharmaceutical Journal 21(1): 55-62, 2018